Profiles of Caregiving Behaviors among Children and Adolescents with Perinatally Acquired HIV - Rabinowitz, Jill A. (AIDS Care, 2019)
Although parenting behaviors are widely considered an important factor in the adjustment of children and adolescents with chronic physical health needs, few studies have addressed this topic as it pertains to youth with perinatally-acquired human immunodeficiency virus (PHIV). We examined profiles of child-centeredness, control through guilt, consistent discipline, and detachment, and whether these profiles differed in terms of parent- and youth-reported psychiatric disorder symptoms in a cohort of HIV infected youth (N=314). Latent profile analyses of caregiving behaviors were conducted separately for children (6–12 years) and adolescents (13–18 years). Two profiles were identified among children: (a) moderate caregiving (87%, n=130) and (b) high detachment caregiving (13%, n=19), and three profiles were identified among adolescents: (a) moderate caregiving (55%, n=88), (b) high detachment caregiving (19%, n=30), and (c) high control through guilt caregiving (26%, n=42). The high detachment and high control through guilt caregiving profiles displayed higher levels of parent-and youth-reported symptoms than the moderate caregiving profile. These findings suggest that caregiver behaviors of PHIV youth vary as a function of children’s developmental period and differ in terms of youth psychological symptoms.